Efektivitas Program Kuliah Tujuh Menit Sebelum Masuk Kegiatan Belajar Mengajar di Mas Al-Islah Bobos - Dinda Barokah Hamdalah; Ica Avrilia; Muhamad Rizal Hasbi; Anggi Yus Susilowati (Indonesian Journal of Islamic Education, 2024)
This study aims to assess the effectiveness of the Seven Minute Lecture program at MAS Al-Islah Bobos in improving students' public speaking skills and active participation. The background of this study is rooted in the challenges faced by students, such as lack of self-confidence and participation in teaching and learning activities. The method used was quantitative with a descriptive approach, involving 64 students as respondents. Data was obtained through a questionnaire survey designed to assess students' level of confidence and engagement. Data analysis was conducted using simple statistics to provide a clear picture of the program results. The findings of this study proved a significant improvement in students' speaking skills and active engagement after attending the seven-minute lecture program. The conclusion of the research is that the Seven Minute Lecture program is effective in improving students' communication skills and self-confidence, so it can be said that the seven-minute lecture program before entering learning activities is effective in helping the process of learning activities of MA Al-Ishlah Bobos students.